Protection of Geographical Indication of Cashew Nut Products in Wonogiri - Sri Rukmanti (Eduvest - Journal of Universal Studies, 2024)
This study describes the challenges of cashew nut geographical indication registration in Wonogiri Regency, Central Java. Wonogiri Regency has great potential as a cashew nut producer that contributes significantly to the regional economy. However, the process of registering geographical indications faces various obstacles, including adequate legal protection and collective awareness of the importance of maintaining the authenticity of local products. This research uses a descriptive analysis approach with a normative juridical method to describe these challenges and propose efforts that can be made by the government and the community to improve the protection of cashew geographical indications. Through the collaboration of various stakeholders, it is expected that Wonogiri Regency can protect and promote cashew nuts as a valuable local heritage and provide sustainable economic benefits for the community.